2022
DOI: 10.3389/fpubh.2022.1012690
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pharmacist-led antimicrobial stewardship program on antibiotic use in a county-level tertiary general hospital in China: A retrospective study using difference-in-differences design

Abstract: BackgroundInappropriate use of antibiotics has become a major driver for the spread of antimicrobial resistance globally, particularly common in China. Antimicrobial stewardship programs are effective in optimizing antimicrobial use and decreasing the emergence of multi-drug-resistant organisms, and the pharmacist has performed a leading role in this program.ObjectiveTo evaluate the impact of antimicrobial stewardship programs driven by pharmacists on antibiotic consumption and costs and the appropriateness of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Pharmacists participate in antimicrobial stewardship, infection prevention and control efforts through clinical efforts focused on the appropriate use of antimicrobial agents and through membership in relevant multidisciplinary workgroups and committees within the healthcare system ( Saseen et al, 2017 ; Lai et al, 2022 ). Currently, pharmacists in China mainly participate in the daily ward rounds in neurosurgery units and review medication regimens ( Zhang et al, 2020b ; Zhang et al, 2021 ; Wang et al, 2022 ; Gu et al, 2023 ). The involvement of pharmacists in patient medical treatment and monitoring is the ideal approach in neurosurgery units because of the complexity of CNSI, the severity of these diseases, and the difficulty of drug selection.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacists participate in antimicrobial stewardship, infection prevention and control efforts through clinical efforts focused on the appropriate use of antimicrobial agents and through membership in relevant multidisciplinary workgroups and committees within the healthcare system ( Saseen et al, 2017 ; Lai et al, 2022 ). Currently, pharmacists in China mainly participate in the daily ward rounds in neurosurgery units and review medication regimens ( Zhang et al, 2020b ; Zhang et al, 2021 ; Wang et al, 2022 ; Gu et al, 2023 ). The involvement of pharmacists in patient medical treatment and monitoring is the ideal approach in neurosurgery units because of the complexity of CNSI, the severity of these diseases, and the difficulty of drug selection.…”
Section: Discussionmentioning
confidence: 99%
“…They play an important role in the development of antibiotics treatment plans according to the PK/PD theory of antimicrobial drugs [18].Other factors needed to be considered include the severity of the patient's condition, site of infection, tissue penetration, antimicrobial drug selection, clinical e cacy, safety, possible pathogenic bacteria, assessment of antimicrobial resistance, protein binding rate, and liver and kidney function. Clinical pharmacist intervention can reduce the rate of unreasonable drug application [19,20,21], shorten the length of hospital stay of patients, lower the incidence of adverse drug reactions, and improve the effect of anti-infection treatment. Daijing Dong et al [22] found the rational rate of prophylactic use of antibiotics in class I incisions was signi cantly improved, and the course of medication was obviously reduced before and after the intervention of clinical pharmacists.Meanwhile, other studies also pointed out [23,24] that the participation of clinical pharmacists in the consultation and individualized adjustment of medication regimens can ensure that patients receive more economic and effective treatment, and have a positive impact on reducing the inhospital mortality of patients with multi-drug resistant infection.…”
Section: Effect Of Re Ned Management Of Antibiotics Led By Clinical P...mentioning
confidence: 99%
“…Many pharmacists in China have been released from conventional dispensing as part of the reform of medical policy. One method for changing medication-related perceptions and increasing the adherence to iron supplements treatment among parents of preterm infants is pharmacist-led education and counseling ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%